EXPLORING ECOSYSTEM WITH MAX AXIOM SUPER SCIENTIST : An Augmented Reading Science Experience - Biskup, Agnieszka; Smith, Tod; Lemke, Donald; Browne, Ronald, Dr. editor (North Mankato, Minnesota : Capstone Press, 2019)
"Trek along with Max as he explores the Earth's many ecosystems. Journeying to the desert, the tundra, even the depths of the sea, young readers will discover the world's many wonderful biomes. Download the free Capstone 4D app for an augmented reality experience that goes beyond the printed page."--Publisher's website.
Includes index
A 4D BOOK
Keywords: Ecology -- Juvenile literature; Ecology